Treatment of effluent textiles with ultraviolet light - Tinoco Gómez, Oscar Rafael (2011)
The use of clean technologies for the treatment of textile effluents is essential to achieve a significant contribution by the textile industry, environmental treatment of them. According to the literature, the dyes used in textile industry are hardly degradable and have strong opposition to biological treatments are subjected to appropriate wastewater. At lower concentrations of hydrogen peroxide (oxygenated water) leads to better dye fading. It also shows that lower concentrations of titanium dioxide system response to the degradation of color, is better, this could be because that lower concentrations of titanium dioxide, hydroxyl radical formation is lower, thus increasing its efficiency the process. The optimum time for color degradation is 2 h and the concentration of titanium dioxide to achieve this time was 50 ppm